Pentingnya Prinsip Komunikasi Kenabian (Kajian Kritis Terhadap Hadis Komunikasi) - Tasbih; Hafid, Saidah A. (Al-Ulum, 2023)
This article describes the principle of prophetic communication in the Hadith. This type of research is qualitative. The primary data source is Kitab Shahih al-Bukhari. in comparison, the secondary data comes from related references. The research instrument uses the HadisSoft application. We discuss ten hadiths on prophetic communication, categorized into three points. Content analysis explicitly and implicitly extracts the principles of prophetic communication in Hadith to conclude. The analysis results show that the focus of prophetic communication is honesty. Honesty is a prophetic identity that must be attached to every form of communication. The implication is that violating honesty as a principle of communication is equivalent to breaking human interests. This article's main contribution is to enrich Hadith's study from the perspective of communication, which is still lacking. Research on the principles of prophetic communication in Hadith can be developed, for example, the ethics of communication between cultures.